Correction to: Building a Children's Health Service and System Research Strategy: development and integration in an Australian paediatric healthcare setting - Robyn Littlewood; Oliver J. Canfell; Frank Tracey (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.